AMYOTROPHIC LATERAL SCLEROSIS – PATHOGENESIS, CLINICAL FEATURES, AND DIAGNOSTIC STRATEGIES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive, fatal neurodegenerative disorder characterized by the selective degeneration of upper and lower motor neurons in the brain and spinal cord. The disease leads to progressive muscle weakness, atrophy, paralysis, and ultimately respiratory failure. This article reviews current knowledge regarding the molecular mechanisms, genetic factors, clinical manifestations, and diagnostic approaches to ALS.